Ongoing Laryngeal Stenosis: Conservative Management and Alternatives to Tracheostomy - Schweiger, Cláudia; Manica, Denise (Frontiers in Pediatrics, 2020)
Background: Following tracheal intubation, some children may develop stridor, which is an indication of an obstructive lesion in the airway, such as an ongoing laryngeal stenosis (LS). This review focuses on evaluation of stridor and possible endoscopic predictors of progression to LS and, once post-intubation acute lesions are established, therapeutic choices to manage this disorder in avoidance of tracheostomy. Tracheostomy, due to its inherent increased morbidity, mortality and influence on social stigma, should be viewed only as a last resort. In this article, available conservative and alternative therapies for ongoing LS are thoroughly reviewed. Methods: A systematic review concerning randomized clinical trials and prospective studies on treatment modalities for LS was performed. A search strategy was developed for MEDLINE comprising terms related to disease, intervention and population. Title and abstract from captured references were peer-reviewed for eligibility. Selected studies full-texts were peer-reviewed and the results were compiled in a structured and narrative review. Stridor evaluation and post-extubation acute lesion classification were studied. Treatments such as balloon dilation, rigid dilation, corticosteroid-coated small tube intubation, and corticosteroid nebulization were described and evidence supporting their usage was discussed.